LMNB1‐related autosomal‐dominant leukodystrophy: Clinical and radiological course. Issue 3 (27th July 2015) - Finnsson, Johannes; Sundblom, Jimmy; Dahl, Niklas; Melberg, Atle; Raininko, Raili
<x xml:space="preserve">Abstract</x> Objective Duplication of the LMNB1 gene encoding lamin B1 causes adult‐onset autosomal‐dominant leukodystrophy (ADLD) starting with autonomic symptoms, which are followed by pyramidal signs and ataxia. Magnetic resonance imaging (MRI) of the brain reveals characteristic findings. This is the first longitudinal study on this disease. Our objective is to describe the natural clinical and radiological course of LMNB1‐related ADLD. Methods Twenty‐three subjects in two families with LMNB1 duplications were studied over two decades with clinical assessment and MRI of the brain and spinal cord. They were 29 to 70 years old at their first MRI. Repeated MRIs were performed in 14 subjects over a time period of up to 17 years. Results Pathological MRI findings were found in the brain and spinal cord in all examinations (i.e., even preceding clinical symptoms). MRI changes and clinical symptoms progressed in a definite order. Autonomic dysfunction appeared in the fifth to sixth decade, preceding or together with gait and coordination difficulties. Motor signs developed ascending from spastic paraplegia to tetraplegia and pseudobulbar palsy in the seventh decade. There were clinical, radiological, and neurophysiological signs of myelopathy. Survival lasted more than two decades after clinical onset. Interpretation LMNB1‐related ADLD is a slowly progressive neurological disease. MRI abnormalities of the brain and spinal cord can precede clinical symptoms by more than a decade and are extensive in all symptomatic patients. Spinal cord involvement is a likely contributing factor to early autonomic symptoms and spastic paraplegia. Ann Neurol 2015;78:412–425